Metabolic complications of policystic ovarian syndrome in menopausal period regarding diabetes mellitus especially - Kos-Kudła, Beata; Staszewicz, Paweł (Menopause Review/Przegląd Menopauzalny, 2002)
Polycystic Ovarian Syndrome is one of the most common endocrinopathy in women of the premenopausal age. Clinical significance of this syndrome is based not only on such a symptoms as menstrual disorders, anovulation, hirsutism, obesity but also metabolic complications manifesting as hiperinsulinemia and insulin resistance, both leading to the development of type 2 diabetes mellitus or cardiovascular complications. Presence of serious metabolic complications of PCOS compells necessity of early diagnosis as well as suitable treatment. Nonpharmacological methods of therapy such as diet and physical exercise leading to weight reduction as well as metformin or thiazolidinediones administration appear to be effective methods of treatment of metabolic dosorders of this syndrome.